2022
DOI: 10.14715/cmb/2021.67.4.10
|View full text |Cite
|
Sign up to set email alerts
|

The signal axis GATA2-EDN1-AGT induced hypertension from obstructive sleep apnea-hypopnea syndrome with the clinical and animal study

Abstract: Hypertension occurred in 50% obstructive sleep apnea-hypopnea syndrome (OSAHS) patients meanwhile OSAHS occurred in 30% hypertension patients. The present study aimed to explore the molecular mechanism of GATA2-EDN1-AGT induced hypertension in the development of obstructive sleep apnea-hypopnea syndrome. OSAHS patients (56 cases: 36 cases of male, 20 cases of female, 42~60 years old) were divided into two groups (case group: patients with hypertension monitored by 24 h ambulatory blood pressure and polysomnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies have revealed that HSPA8 [262], HSP90AA1 [259], MYH9 [339], SORT1 [335], ACTA2 [307], SOX2 [773], SMAD4 [774], GATA2 [775], CCND1 [776], SPI1 [777] and SMARCA4 [778] plays a key role in cardiovascular diseases. The altered expression of HSPA8 [174], MYH9 [209], FLNA (filamin A) [444], SOX2 [779], GATA2 [780], EP300 [781] and SMARCA4 [782] plays a key role in the progression of hypertension. HSPA8 [600], MYH9 [647], CDH1 [630], SORT1 [643], ACTA2 [626], RARA (retinoic acid receptor alpha) [656], hsa-mir-152-3p [783], SOX2 [784] and EP300 [785] are mainly associated with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that HSPA8 [262], HSP90AA1 [259], MYH9 [339], SORT1 [335], ACTA2 [307], SOX2 [773], SMAD4 [774], GATA2 [775], CCND1 [776], SPI1 [777] and SMARCA4 [778] plays a key role in cardiovascular diseases. The altered expression of HSPA8 [174], MYH9 [209], FLNA (filamin A) [444], SOX2 [779], GATA2 [780], EP300 [781] and SMARCA4 [782] plays a key role in the progression of hypertension. HSPA8 [600], MYH9 [647], CDH1 [630], SORT1 [643], ACTA2 [626], RARA (retinoic acid receptor alpha) [656], hsa-mir-152-3p [783], SOX2 [784] and EP300 [785] are mainly associated with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%